Environmental consequences associated with collisions involving double hull oil tanker - Kim, Yang Seop; Youssef, Samy; Ince, Serdar; Kim, Sang Jin; Seo, Jung Kwan; Kim, Bong Ju; Ha, Yeon Chul; Paik, Jeom Kee (TAYLOR & FRANCIS LTD, 2015)
As the total world trade of oil by tankers grow, the potential risk to the marine environment increases. When oil tankers are involved in accidents (e.g., collision or grounding), a consequence of the resulting damage could be the release of crude oil or petroleum products into the sea. The aim of the present study is to investigate the environmental consequences of the involnement of oil tankers in collision. Using probabilistic approaches, credible scenarios of ship-ship collision are selected to create a representative sample of the most possible ones. The LS-DYNA non-linear finite element method is used to predict the resulting damage or opening associated with the individual scenarios. The environmental consequences are then estimated by calculation of the amount of oil spilled in each scenario. In addition, the potential damage to the environment is presented in terms of monetary units that can be understandable to all stakeholders.
Keywords: double hull oil tanker; collision; oil outflow; environmental effect; SPILLS; COST; Engineering